Pandemic disruptions to access to higher education in South Africa: A dream deferred? - Menon, K.; Motala, S. (South African Journal of Higher Education, 2022)
The COVID-19 pandemic and the shift to emergency remote teaching (ERT) and online learning highlighted issues of social justice, pedagogical inclusion and epistemic access in higher education. The research underlying this article analyses the complexities of access to learning and the effects of the shift to ERT and online learning on the social justice agenda in South Africa, using the case study of the University of Johannesburg. The article uses the conceptual frameworks of epistemic access, equity and inclusive pedagogy from the theories of Fraser (2008), Mbembe (2016) and Mgqwashu (2016). Pedagogic continuity and inclusion (Motala and Menon 2020; Menon and Motala 2021), hard-won by many institutions during the pandemic, will need to be sustained and secured as the world adapts to a “new normal” in higher education and other spheres of life. Czerniewicz et al. (2020, 957) refer to the maxim “Anytime, anyplace, anywhere” characterising ERT as a “brutal underestimation of the complexities and entanglement of different inequalities and structural arrangements”. Fataar (2020), Czerniewicz et al. (2020) and Hodges et al. (2020) advocate an alternative pedagogy that is “trauma-informed” and offers parity with the pedagogies that prevailed pre-pandemic. The article concludes that the pre-existing conditions of deep inequality and inequities, and a highly differentiated higher education system with uneven pedagogical practices, were exacerbated by the pandemic. While we acknowledge the achievement of avoiding the loss of the academic year during the pandemic, we argue that it is important to learn lessons from the initial implementation of ERT and the fractures that it highlights in higher education. Heading into an uncertain future, the sector needs explicit equity-driven approaches to ensure pedagogical inclusion beyond physical and epistemic access.